G237 Why Do Children with Gastroenteritis Present to Emergency Departments?. (4th June 2013) - Taylor, CA; Williams, C; Pyper, S; Mehta, BM; Marzouk, O; Sutcliffe, A
Abstract : Aims: Gastroenteritis is a significant cause of morbidity and mortality worldwide. It accounts for 10–20% of presentations to urgent and emergency care annually in the UK. Surprisingly little is known about parental expectations of care and the factors that lead to presentations by children with gastroenteritis. In this study we sought to investigate these factors in the paediatric emergency department (ED) setting. Methods: We conducted our study within the EDs of two large tertiary hospitals, each within a major UK city during January-March 2012. An opportunistic sample was taken. Parents/carers with children aged from six months to their fifth birthday presenting with suspected gastroenteritis were eligible. The study questionnaire was designed by the authors, informed by the available literature. In order to improve validity, the questionnaire was piloted on a small sample of parents and additionally reviewed by the National Institute for Health Research Clinical Specialities Group in general paediatrics. Results: The questionnaire was completed by 121 parents across the two hospitals. Parents were asked for the main reason that they had brought their child to the ED. Of seven possible responses, the most frequently chosen, was 'symptoms persisted longer than expected' (by 56%), however 46% wanted 'reassurance that there is not a serious cause'. When making the decision to come to the ED, 46% had decided alone, 40% were helped by a healthcare professional and 15% were helped by a family member. Asked about investigation expectations, 31% were expecting urine tests and 21% were expecting blood tests. Many parents were expecting treatments to be given including 38% expecting an anti-emetic, 34% an anti-diarrhoeal agent, 11% antibiotics and 55% fluids (36% by mouth, 13% intravenously or 6% nasogastrically). When we asked what would make parents confident about going home, the most common response was 'after reassurance that the child is not dehydrated'. Other responses referred to advice or physical symptoms. Conclusion: Knowledge of parental expectations provided by this study, particularly with regard to expectations of investigations and treatment could enable physicians to provide more comprehensive care, with particular emphasis on explanation. This may improve parental satisfaction and reduce re-attendance.